Association between air pollution and type II diabetes in Italy from clinical data and population-weighted exposure at the municipality level - Cristiana Abbafati; Luciano Nieddu; Giorgio Cattani; Maria Antonietta Reatini; Paola Ponzani (Scientific Reports)
Abstract A growing body of literature supports the association between ambient particulate pollution and the risk of type 2 diabetes (T2DM). Both issues are particularly relevant in Italy. This study investigates the relationship between T2DM and exposure to PM2.5 and PM10 in Italian municipalities from 2013 to 2021. Data on T2DM were provided by the Italian Association of Diabetologists (AMD), representing the only national outpatient dataset not based on self-reported information. Air pollution data, sourced from the Italian Institute for Environmental Protection and Research, ISPRA, were summarized using the population-weighted exposure (PWE) indicator. Both datasets were made available through a dedicated research agreement. Random effects models and non-parametric methods were applied to assess the association between air pollution and T2DM. Results indicate a statistically significant relationship, particularly between T2DM and PM2.5. T2DM incidence rates were significantly negatively associated with time (coefficient = − 0.07961, p < 0.01), indicating a decreasing trend over time. After adjusting for other covariates, PM10 population-weighted exposure was not significantly associated with incidence rates (coefficient = − 0.00057, p = 0.58). On the other hand, increases in the ratio of PM2.5 to PM10 (pwratio) were significantly positively associated with increases in T2DM incidence rates (coefficient = 0.52304, p < 0.01) at the municipal level. T2DM prevalence proportions were significantly positively associated with time (coefficient = 0.01749, p < 0.01), suggesting an increasing trend over time. PM10 was significantly negatively associated with prevalence proportions (coefficient = − 0.00298, p = 0.03), while increases in pwratio were significantly positively associated with increases in prevalence proportions (coefficient = 0.18724, p < 0.01). Thus, municipalities with a higher share of PM2.5 within the same level of PM10, tended to show higher T2DM prevalence proportions and incidence rates, consistent with the spatial distribution of air pollution and disease burden observed across Italy.